Microsurgical strategies after free flap failure in soft tissue reconstruction of the lower extremity: a 17-year single-center experience - Strübing, Felix; Xiong, Lingyun; Bigdeli, Amir K.; Diehm, Yannick; Kneser, Ulrich; Hirche, Christoph; Gazyakan, Emre (Journal of Personalized Medicine, 2022)
Background: There is no clear consensus on the optimal surgical strategy for providing safe coverage in salvage free flap surgery after total free flap failure. Methods: A retrospective study was conducted to evaluate patients with total failure of the primary free flap in lower extremity reconstruction between 2000 and 2017. Results: In a cohort of 1.016 patients, we identified 43 cases of total flap failure (4.2%). A total of 30 patients received a salvage free flap with a success rate of 83.3% (25/30). One patient received a secondary salvage free flap. Overall limb salvage after primary free flap loss was 83.7% (36/43). Conclusions: Microsurgical management of free flap loss in the lower extremity is challenging and requires a decisive re-evaluation of risk factors and alternative strategies. This should include reconsidering the flap choice with a tendency towards traditional and safe workhorse flaps, a low-threshold switch to different recipient vessels, including arteriovenous (AV) loops, bypasses (especially in case of venous insufficiency) and back-up procedures, such as negative pressure wound therapy or dermal regeneration templates with skin grafting in cases of lower demand and critically ill patients. We derived one suggestion from our previous practice: replacing perforator flaps with axial pattern flaps (“safe workhorses”).